COMPARISON OF INHIBITORY ACTIVITY OF KELAKAI LEAVES EXTRACT WITH Ciprofloxacin AGAINST Aggregatibacter actinomycetemcomitans ATCC® 6514™ - Dyah Setyorini; I Wayan Arya K. Firdaus; Beta Widya Oktiani (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Aggressive periodontitis is an inflammatory disease that exhibit rapid destruction of periodontal tissue and alveolar bone. The disease is caused by several factors, one of them is Aggregatibacter actinomycetemcomitans. The treatment to reduce the growth of Aggregatibacter actinomycetemcomitans is by giving spesific antibiotic like ciprofloxacin. Frequent and inappropriate use of antibiotics can cause side effects, so it needs alternative medicine that have antibacterial activity like kelakai leaves. Ethanol extract of kelakai leaves contains antibacterial compounds, such are flavonoid, tannin, steroid and alkaloid. Objective: The aim of this study was to compare the inhibitory activity of kelakai leaves extract (Stenochlaena palustris) with ciprofloxacin against Aggregatibacter actinomycetemcomitans. Method: This study was true experimental design with  post-test only design. The inhibitory activity test was performed using diffusion method in 5 treatment groups and 4 repetitions. The treatment groups were kelakai leaf extract with 25%, 50%, 75%, 100% concentrations  and 5µg ciprofloxacin. Inhibitory activity was measured by calculating the diameter of the clear zone (mm) that was formed on MHA. Results: The highest inhibition zone of kelakai leaf extract which found at concentration of 100% was 14.45 mm and the inhibition zone of ciprofloxacin was 26.28 mm. One way Anova test result (P = 0,000) and post hoc LSD test proved that there were significant differences of inhibition zones in each treatment group. Conclusion: Ethanol extract of kelakai leaves with concentration of 25%, 50%, 75% and 100% have inhibitory activity against Aggregatibacter actinomycetemcomitans but it is not as strong as ciprofloxacin.